Malaysia’ 14th general election: end of an epoch, and beginning of a new? - Moniruzzaman, Md.; Farzana, Kazi Fahmida (IIUM Press, International Islamic University Malaysia, 2018)
The 14th general election in Malaysia held on May 9, 2018 is an historic event that altered the political landscape of the nation. For the first time over sixty years this election has caused to change the government from Barisan Nasional (national front) coalition to another coalition named Pakatan Harapan (Coalition of Hope), formed in 2015. This article has analysed the election results and the probable factors that might have contributed to the historic change. It argued that since 1999 the ruling Malay elites have become permanently divided challenging the dominance of United Malay National Organisation (UMNO) in politics and the prospect for a viable alternative became consolidated with the rise of Parti KeAdilan Rakyat (PKR) offering an avenue for a new generation politics. The return of Mahathir Mohamad to politics and a strategic coalition mainly between his party and PKR, party of the jailed leader Anwar Ibrahim, made an alternative to BN/UMNO a reality through winning the election.